A parceria público-privada no acesso à educação infantil no município de Santa Cruz do Sul/RS: impasses e contradições - Foletto, Andrielli Leal (2023)
This Professional Master's dissertation, from the Postgraduate Program in Public Policies and Educational Management, research line 1 - Policies and Management of Basic and Higher Education, addresses the issue of public-private partnerships in Early Childhood Education in the municipality of Santa Cruz do Sul/RS, with the aim of analyzing the public-private partnership policy in the municipality of Santa Cruz do Sul/RS from the perspective of educational quality. Its specific objectives are: the municipal education system of Santa Cruz do Sul, with regard to the provision of Early Childhood Education; to investigate how the municipality of Santa Cruz do Sul has been allocating FUNDEB resources to partner schools; to analyze how the legal acts of the municipal education network of Santa Cruz do Sul establish a public/private partnership relationship with accredited schools. It is based on a qualitative research approach, carried out in the municipal education network in Santa Cruz do Sul, based on research with members of the municipality's education department, and with the management of accredited schools, using the techniques of bibliographical research, semi-structured interviews, technical visits and questionnaires. The theoretical framework of the research is organized based on the authors Saviani (2008) and Yin (2001), national and regional legislation and authors such as Campos (2011), Moss (2003), Peroni (2019), Oliveira (2015). The product produced is a manual of guidelines/recommendations for accredited schools in the municipality of Santa Cruz/RS. In view of this, we analyzed that the growing decentralization of the state has increased the responsibilities of the municipality in relation to Early Childhood Education, observing its demand and the possibilities of meeting it, has opened up space for public-private partnerships.